Use of the chemical peeling technique for cassava-parsley (Arracacia xanthorrhiza B.) and evaluation of efficiency (Research, Society and Development, 2021)
The cassava-parsley has a high nutritional value, it is easy to digest, therefore, very assigned to children, the elderly, pregnant women and people with special diets. The roots are not uniform, there are differences in size, shape and weight, and due to these characteristics, industrial equipment normally used in vegetable peeling operations, such as the abrasion process, are not viable for this tuber. Thus, an application of the chemical peeling process with sodium hydroxide solution is the most suitable. The present proposal sought to optimize the chemical peeling process of parsnip, considering the process variables - temperature and NaOH concentration and contact time. The results obtained by response surface methodology, through a central rotational composite experimental design. The results were expressed considering the pulp loss and the peeling performance. For both evaluations, an analysis of variance revealed that only the linear effect of time had a degree of significance (p